19th-century foreign-language names of residents of Piotrków Trybunalski with the suffix -er - Klimas, Agnieszka (Papers in Linguistics, 2021)
This article is devoted to non-Polish personal names gathered in the SNMP and containing the suffix -er. The undertaken analysis shows that these names are characteristic of people of Jewish or German origin.. Their derivative bases are: Hebrew names, personal names gathered in the SNMP and Jewish and German anthroponomic dictionaries, Germanized and native local names from different parts of Poland, local names from different parts of Europe and German and Yiddish appellativa. Foreign surnames with the suffix -er represent such cognitive categories as: kinship, origin, appearance and character. These surnames sometimes belong to two or three cognitive categories simultaneously and create homonymous relations.